Tourist Attitudes Towards Online Tourism Marketing Promotion of Phu Pha Man Tourism National Park, Khon Kaen Province - Polnyotee , Maythawin; thetseeha, klitsana; Rodkhanmuang, Daungmuneeporn (KKBS Journal of Business Administration and Accountancy, 2025)
This research aimed to 1) analyze tourists' attitudes towards the promotion of tourism marketing through online media of Phu Pha Man National Park, Khon Kaen Province, and 2) propose guidelines for the promotion of marketing through online media of Phu Pha Man National Park, Khon Kaen Province. The quantitative sample consisted of 400 local tourists and the qualitative sample consisted of 3 persons from 2 government officials: the Tourism Authority of Thailand and the National Park officials. The results indicate that most tourists have a positive attitude toward online marketing due to its quick and convenient information, such as engaging photos and videos. Online marketing helps tourists plan their trips more easily, such as by checking routes and activities. Additionally, reviews from other tourists serve as an essential source of information for decision-making. Interviews focused on using online media to promote tourism, public relations strategies, conservation planning for local resources, and the development of online channels such as Facebook and websites. Collaboration with the private sector and local communities is also suggested to create sustainable tourism activities. The guidelines for promoting online marketing include using social media as the main channel for public relations, such as video reviews, live broadcasts, and using online influencers, as well as developing easy-to-use websites and applications that support multiple languages ​​to attract international tourists.